Association between adiponectin concentrations and cardiovascular disease in diabetic patients: a systematic review and meta-analysis. - Zhenjie Wu; Yunjiu Cheng; Lynn Htet Htet Aung; Bixun Li (PLoS ONE)
Background This systematic review and meta-analysis of prospective studies evaluates the association between adiponectin concentrations and risk of cardiovascular disease (CVD) in individuals with diabetes mellitus (DM). Methods PubMed and Embase were searched for prospective studies on the association of adiponectin concentrations and risk of CVD up to June 2013. Random-effect model was selected to pool the relative risk (RR) and 95% CI. Results Five prospective cohort studies and one nested case-control studies met the included criterion. The estimated summary RR and 95% CI of five prospective cohort studies for type 2 diabetes comparing top vs low tertile of adiponectin concentrations was 0.99 (95% CI: 0.67-1.45), with significant heterogeneity between studies (p = 0.037, I (2) = 60.9%). This heterogeneity was explained by one study conducted in Korean. Conclusions This study represents the first meta-analysis between adiponectin levels and CVD in diabetic patients and indicated no association was found. This result should be verified further by large sample size, long duration of follow-up, and well-designed prospective clinical trials.